Modeling for understanding of coronavirus disease-2019 (COVID-19) spread and design of an isolation room in a hospital - Wu,X; Abubakar-Waziri,H; Fang,F; Dilliway,C; Wu,P; Li,J; Yao,R; Bhavsar,P; Kumar,P; Pain,CC; Chung,KF (Physics of Fluids, 2023)
We have modeled the transmission of coronavirus 2019 in the isolation room of a patient suffering from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the Royal Brompton Hospital in London. An adaptive mesh computational fluid dynamics model was used for simulation of three-dimensional spatial distribution of SARS-CoV-2 in the room. The modeling set-up is based on data collected in the room during the patient stay. Many numerical experiments have been carried out to provide an optimal design layout of the overall isolation room. Our focus has been on (1) the location of the air extractor and filtration rates, (2) the bed location of the patient, and (3) consideration of the health and safety of the staff working in the area.